(untitled) (Journal of the College of Basic Education, 2022)
The carpet industry is one of the most famous and oldest handicrafts in Iraq. The research dealt with an introduction that shows the main steps of the research with some defining concepts. The research focused on three main points as follows:First: - Presentation of an overview of the origins of carpets and the history of the establishment of the Handmade Carpet Factory.Second: It deals with the method of making handmade carpets from warp work to kilim work at the end of the carpet.Third: It included a review of the spatial components of the settlement of the handmade carpet factory in the province of Baghdad - Al-Kadhimiya, as it took the preparation of the labor force (2008-2015) and its changes, as well as dealing with the market and its role in the disposal of the product, its marketing destinations and the company’s sales in 2015